Design of a counter torque device used in a torque standard machine = Erzeugung des gegendrehmoments in einer drehmoment-normalmesseinrichtung - Pino Samalvides, Eduardo Anibal (Pontificia Universidad Católica del Perú, 2017)
In the last years, the increase in the need of higher accuracy in science, research and technology in precision engineering created an obligation to produce a new torque standard machine for precise measurement of torque. This thesis deals with the design and implementation of a Counter Torque Device which will be used in a new Torque Standard Machine based on moving mass developed in the faculty of precision engineering at the TU Ilmenau. This new Torque Standard Machine must have a measuring range from 1 mNm to 1 Nm and a lower relative uncertainty Ur :S 1x1O-5 (k = 2). In order to achieve this aim, the fundamentals and the state of the art are shown at the beginning of the thesis. After the specific requirements are compiled in a requirements list, then based on physical and technical principles different possible solutions are developed and evaluated, from this evaluation optimal solution is founded, implemented and tested.
Keywords: Convertidores de Torque--Diseño y construcción; Calibración; https://purl.org/pe-repo/ocde/ford#2.03.01